Africa's changing agricultural development strategies - Delgado, Christopher L. (International Food Policy Research Institute, 1997)
During the last 25 years, African policymakers have been bombarded with often conflicting advice on agricultural development strategy from an increasing array of international development agencies. In this brief, Christopher Delgado gives a chronology of agricultural paradigms for Africa. He points out that agricultural development paradigms have gone back and forth between defining agriculture as the engine for growth through cash and export cropping, and emphasizing food production, import substitution, and food self-sufficiency. . Each paradigm has left an intellectual heritage, and today there is some consensus on the issues of importance. Development practitioners now generally agree on the need to increase agricultural productivity, lower high transportation and rural transfer costs, increase rural employment, integrate remote and lower-potential areas (about 80 percent of cropped area) into the national growth strategies, and ensure that Africans design and implement future strategies.